Effects of Nonsurgical Spinal Decompression Treatment on the Level of Pain and Quality of Life in Patients with Cervical or Lumbar Disc Herniation: A Retrospective Observational Study - Beom Seok Kim; Ye Ji Lee; Hyo Bin Kim; Ki Jung Sung; Ju Hyun Jeon; Eun Seok Kim; Young Il Kim (MEDrang Inc., 2020)
Background This study aims to statistically analyze and compare the curative effect and satisfaction level between typical traditional Korean medicine treatment and nonsurgical spinal decompression treatment. Methods Of the patients who were diagnosed with the cervical or lumbar herniated intervertebral disc at the Department of Acupuncture and Moxibustion Medicine at the Daejeon Korean Medicine Hospital from April 14th to August 25th, 2019, this study retrospectively analyzed the medical records of 31 patients who underwent nonsurgical spinal decompression treatment and traditional Korean medicine (assigned to Group A) and another 31 patients who received typical traditional Korean medicine alone (assigned to Group B). The clinical data were analyzed using IBM SPSS Version 23.0. Results No statistically significant differences appeared in terms of sociodemographic, condition, and therapeutic characteristics, except whether the patient received Western medicine treatment, before or after a treatment with traditional Korean medicine. Group A exhibited higher variations in numeric rating scale, EuroQol- 5 dimension and EuroQol visual analogue scale scores compared to Group B as determined by independent sample t test and analysis of covariance. In addition, the satisfaction score of Group A was higher than that of Group B The result of cross analysis revealed that desire for continued treatment in Group A was higher than that of Group B. Conclusion This retrospective observational study showed that the patients with nonsurgical spinal decompression treatment reported a greater reduction in pain, improved quality of life and satisfaction than patients receiving typical traditional Korean medicine.